Renewal and Return to the Center - Simcox, Kristian Shea (Cosmos and History: The Journal of Natural and Social Philosophy, 2021)
In a 2004 essay, "What Coyote and Thales Can Teach Us: An Outline of American Indian Epistemology,” Brian Yazzie Burkhart suggests an educational value of the natural world, noting that "the most important things to keep in mind are the simple things that are directly around us in our experience,” and that "truth ... and meaning and value arise in the intersection between us and all that is around us.” Burkhart offers these insights in an essay dedicated to showing ways in which Native American philosophy differs from Western philosophy. My paper, while maintaining a respect for that difference, approaches the work of two 19th-century Western thinkers”Schelling and Emerson”through a framework suggested by Burkhart and other Native American philosophers. I do so with the aim of bringing to the foreground possibilities for contemporary environmental philosophy. The central focus of the paper is the educational value of our interactions with nature: the ways in which our self-understanding”and along with it, our moral disposition”might be transformed through our interactions with the natural world. Schelling and Emerson have each been acknowledged for the ways in which their work prefigures contemporary environmentalism, and indigenous American worldviews are recognized for their prospects of rehabilitating our relationship to nature. This paper argues for a renewed sense of self in nature emerging from the contributions of all three. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->